2007
DOI: 10.1037/0096-1523.33.1.209
|View full text |Cite
|
Sign up to set email alerts
|

Transposed-letter effects in reading: Evidence from eye movements and parafoveal preview.

Abstract: Three eye movement experiments were conducted to examine the role of letter identity and letter position during reading. Before fixating on a target word within each sentence, readers were provided with a parafoveal preview that differed in the amount of useful letter identity and letter position information it provided. In Experiments 1 and 2, previews fell into 1 of 5 conditions: (a) identical to the target word, (b) a transposition of 2 internal letters, (c) a substitution of 2 internal letters, (d) a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
201
5
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(232 citation statements)
references
References 58 publications
(143 reference statements)
15
201
5
3
Order By: Relevance
“…Orthographic processing difficulty may result from letter sequences that are either illegal or infrequently encountered at a particular position. This kind of account would offer possible explanatory power for research demonstrating the flexibility of letter encoding during reading and nonreading tasks (Johnson & Dunne, 2012;Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthographic processing difficulty may result from letter sequences that are either illegal or infrequently encountered at a particular position. This kind of account would offer possible explanatory power for research demonstrating the flexibility of letter encoding during reading and nonreading tasks (Johnson & Dunne, 2012;Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate parafoveal previews have also been shown to increase the probability that words will be skipped during first-pass reading (Angele & Rayner, 2011;Angele, Slattery, Yang, Kliegl, & Rayner, 2008). In addition, previous research has revealed the particularly important role of initial letter sequences for parafoveal processing (Johnson, Perea, & Rayner, 2007;Rayner, 1975;White, Johnson, Liversedge, & Rayner, 2008). Because of the sharp decline in acuity outside the fovea, parafoveal processing is most likely to be affected by the initial letters of parafoveal words.…”
mentioning
confidence: 99%
“…In the context of an eye-movement study, Johnson, Perea, and Rayner (2007) reinvestigated the role of the final letters during parafoveal preprocessing by either transposing or substituting (i.e., applying a different letter mask) the final two letters of five-letter words during parafoveal preview. The critical finding was that the manipulation of the final letters led to prolonged fixation times compared to a valid preview.…”
mentioning
confidence: 99%
“…standard naming and lexical decision tasks generalize to word recognition processes while reading" (p. 392) (e.g., see Acha & Perea 2008b;Davis et al 2009;Johnson, Perea, & Rayner, 2007;Perea & Pollatsek 1998, for a few instances). Furthermore, single-word identification tasks provide ecologically valid information (e.g., when we process sign roads, the name of bus/subway stations, names of products/stores, etc).…”
mentioning
confidence: 99%